2009
DOI: 10.1148/radiol.2521081682
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Detection with Dual-Energy CT: Experimental Study of Dual-Source CT in Rabbits

Abstract: Dual-source CT can depict normal and abnormal blood perfusion distribution in a rabbit's lung. Abnormal pulmonary blood distribution, as shown at dual-source CT, improves detection of acute PE in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 39 publications
0
77
0
Order By: Relevance
“…In some segmental arteries with non-occlusive tiny mural thrombus, the PBV image may be normal and this is the reason for false-negative results. In an experimental PE model in rabbits, Zhang et al [4] reported that the diagnostic sensitivity of PBV imaging alone in the detection of PE was 87% and had a good correlation with pathological analysis. In contrast to PBV imaging, CTA had a lower sensitivity of 67%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some segmental arteries with non-occlusive tiny mural thrombus, the PBV image may be normal and this is the reason for false-negative results. In an experimental PE model in rabbits, Zhang et al [4] reported that the diagnostic sensitivity of PBV imaging alone in the detection of PE was 87% and had a good correlation with pathological analysis. In contrast to PBV imaging, CTA had a lower sensitivity of 67%.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of dual-source CT means that simultaneous evaluation of lung parenchyma perfusion and vascular blockage is now feasible. It has been shown to be a reliable method, with only one CT scan, in animal experiments [4] and clinical practice [5][6][7]. Besides lung parenchyma perfusion and arterial obstruction, right ventricular function is also an important tool for assessment of severity and is a predictor of mortality [8,9] in acute PE patients.…”
mentioning
confidence: 99%
“…Pontana et al [16] also showed that the presence of endoluminal thrombus is associated with pulmonary perfusion defects at DECT. In an experimental study by Zhang et al [22], conventional CTPA identified pulmonary emboli in only 12 and the absence of emboli in 18 pulmonary lobes, corresponding to a sensitivity and specificity of 67% and 100%. By contrast, DECT and BFI each correctly identified pulmonary emboli in 16 of 18 pulmonary lobes and reported the absence of emboli in 11 of 12 lobes, corresponding to sensitivity and specificity of 89% and 92% for detecting pulmonary emboli.…”
Section: Detection Of Pementioning
confidence: 99%
“…[1][2][3] Pulmonary embolism is a common cause of pulmonary IRI (PIRI), and the incidence of pulmonary embolism is increasing 4,5 with a mortality rate of up to 30%. 6 With timely identification and treatment of pulmonary embolism, mortality rates can be reduced to ,10%.…”
mentioning
confidence: 99%